2012
DOI: 10.1007/s11999-012-2367-7
|View full text |Cite
|
Sign up to set email alerts
|

A Promising Thumb Basal Joint Hemiarthroplasty for Treatment of Trapeziometacarpal Osteoarthritis

Abstract: BackgroundTrapeziometacarpal joint osteoarthritis is a painful, disabling condition that primarily affects women who are postmenopausal. Arthroplasty has been performed to treat this condition; however, subluxation has been a problem with all previous implants. We report the results of hemiarthroplasty using a prosthesis designed to address the problems associated with previous implants.Questions/purposesWe wished to (1) determine if this prosthesis results in pain relief and functional improvement and preserv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 22 publications
1
27
0
1
Order By: Relevance
“…All these reports used a dorsoradial incision between EPB and APL. [36][37][38][39][40][41][42] The only study using a posterolateral approach for implantation of a ball and socket prosthesis and reporting de Quervain in the first year following implantation was that of Ulrich-Vinther et al 26 The unique mobility of the thumb contributes to the syndrome. 43 An awkward wrist position is also generally accepted as a condition related to de Quervain disease.…”
Section: Discussionmentioning
confidence: 99%
“…All these reports used a dorsoradial incision between EPB and APL. [36][37][38][39][40][41][42] The only study using a posterolateral approach for implantation of a ball and socket prosthesis and reporting de Quervain in the first year following implantation was that of Ulrich-Vinther et al 26 The unique mobility of the thumb contributes to the syndrome. 43 An awkward wrist position is also generally accepted as a condition related to de Quervain disease.…”
Section: Discussionmentioning
confidence: 99%
“…Time for return to full unrestricted activity was only mentioned in five of the 19 studies (Table 5) [6,12,14,16,19]. The range for time to return to full activity was 5 to 12 weeks in these studies.…”
Section: Resultsmentioning
confidence: 95%
“…Postoperative thumb exercise protocols were quite variable across the studies identified (Table 4). Some patients simply were shown exercises after the immobilization was discontinued [2,5,8,12,13,15,19]. Patients in other studies were referred to a therapist after the period of immobilization [1,3,4,7,9,24].…”
Section: Resultsmentioning
confidence: 99%
“…[113][114][115][116] However, an independent study by Perez-Ubeda et al reported 70% failure in 20 implants followed for between 24 and 45 months, with loosening in 55% and ankylosis in 15%. 122 Interposition arthroplasty at the base of the thumb with pyrocarbon implants has been studied using a number of forms including spheres, ellipsoids and tori or 'doughnuts' that are inserted by reaming the trapezium to create a cup. 118 Good outcomes were also reported at a mean of 59 months with only one patient complaining of minimal pain, and one revision for post-traumatic loosening.…”
Section: Reported Outcomes: First Carpometacarpal Jointmentioning
confidence: 99%